The role of vaccination route with an adenovirus-vectored vaccine in protection, viral control, and transmission in the SARS-CoV-2/K18-hACE2 mouse infection model - Dickson, Alexandria; Geerling, Elizabeth; Stone, E. Taylor; Hassert, Mariah; Steffen, Tara L.; Makkena, Taneesh; Smither, Madeleine; Schwetye, Katherine E.; Zhang, Jianfeng; Georges, Bertrand; Roberts, M. Scot; Suschak, John J.; et al. (Frontiers in Immunology, 2023)
Vaccination is the most effective mechanism to prevent severe COVID-19. However, breakthrough infections and subsequent transmission of SARS-CoV-2 remains a significant problem. Intranasal vaccination has the potential to be more effective in preventing disease and limiting transmission between individuals as it induces potent responses at mucosal sites. Utilizing a replication-deficient adenovirus serotype 5-vectored vaccine expressing the SARS-CoV-2 RBD (AdCOVID) in homozygous and heterozygous transgenic K18-hACE2, we investigated the impact of route of administration on vaccine immunogenicity, SARS-CoV-2 transmission, and survival. Mice vaccinated with AdCOVID via the intramuscular or intranasal route and subsequently challenged with SARS-CoV-2 showed that animals vaccinated intranasally had improved cellular and mucosal antibody responses. Additionally, intranasally vaccinated animals had significantly better viremic control, and protection from lethal infection compared to intramuscularly vaccinated animals. Notably, in a novel transmission model, intranasal vaccination reduced viral transmission to naive co-housed mice compared to intramuscular vaccination. Overall, our data provides convincing evidence for the use of intranasal vaccination in protecting against SARS-CoV-2 infection and transmission.